Index Onomastsique/Author Index - Abeytunga, P. K.; Auger, R.; Auster, E.; Berube, J. E.; Bolduc, R.; Bregzis, R.; Brunet, L.; Campbell, J. L.; Carroll, J.; Cartier, C.; Choul, J. C.; Currie, B.; et al. (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l'ACSI, 2022)
See PDF